2000
DOI: 10.1111/j.1540-8159.2000.tb07070.x
|View full text |Cite
|
Sign up to set email alerts
|

ICD Waveform Optimization: A Randomized, Prospective, Pair‐Sampled Multicenter Study

Abstract: MOUCHAWAR, G., ET AL.: ICD Waveform Optimization: A Randomized, Prospective, Pair-Sampled Mul ticenter Study. The theoretical tissue model-based estimates of phase 1 and phase 2 duration of biphasic waveforms are considerably shorter than the pulse widths currently used in ICDs with standard tilt. This study used a tissue resistance/capacitance (RC) model to identify optimal biphasic pulse widths. By paired step-down defibrillation threshold (DFT) testing, the efficacy of standard versus "tuned" biphasic wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 13 publications
1
39
2
Order By: Relevance
“…Fixed pulse-width waveforms have been shown to provide lower voltage and energy DFTs than fixed-tilt waveforms, particularly when DFT is higher than 400 V. This might explain our lower DFT per LVEF range as well as our lower incidence of ‘high DFT’. 21,22 It should be noted that concerns regarding DFTs between 20 and 26 J may not be as great when a device with maximum delivered energy capability of 36 J is used because a 10 J safety margin would be available.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed pulse-width waveforms have been shown to provide lower voltage and energy DFTs than fixed-tilt waveforms, particularly when DFT is higher than 400 V. This might explain our lower DFT per LVEF range as well as our lower incidence of ‘high DFT’. 21,22 It should be noted that concerns regarding DFTs between 20 and 26 J may not be as great when a device with maximum delivered energy capability of 36 J is used because a 10 J safety margin would be available.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the frequency analyses were performed using induced VF under general anesthesia, the electrophysiological characteristics of which may differ from those of spontaneous VF (31). The defibrillation threshold is affected by variables of the ICD system, such as the number of defibrillation coils and position of the defibrillation lead and ICD (32)(33)(34). However, in the current study, the ICDs and leads were positioned similarly in all patients, and the number of defibrillation coils did not affect the DF or defibrillation threshold.…”
Section: Study Limitationsmentioning
confidence: 99%
“…There is inter‐patient variability in the critical membrane time constant (τ) for defibrillation [106]. Most studies of optimized waveforms use phase durations based on an assumed typical human critical membrane time constant of 3.5 ms. Human studies have now confirmed the superiority of fixed duration waveforms over tilt‐based duration waveforms [107–110].…”
Section: Optimal Pulse Widthsmentioning
confidence: 99%